(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2012)
The paper presents the development assessment system tracks peredichi information in the mesh network and routing algorithm that uses data evaluation. Using this algorithm reduces the interference in the network and power consumption. Provides resistance to changes in the network.